PENGARUH METODE EKSTRAKSI DAN PELARUT TERHADAP KANDUNGAN METABOLIT SEKUNDER DAN AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN INSULIN (Smallanthus sonchifolius): SOLVENTS EFFECT AND EXTRACTION METHODS ON SECONDARY METABOLITE CONTENT AND ANTIOXIDANT ACTIVITY OF INSULIN LEAF EXTRACT (Smallanthus sonchifolius) - Saputri, Alip Desi Suyono; Sa'ad, Muhammad; Maharani, Putri; Prahesti, Maya Tesa (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2024)
Insulin leaves (Smallanthus sonchifolius) are reported to have strong antioxidant activity. This activity comes from the content of secondary metabolite compounds such as phenolics, flavonoids, tannins, as well as anthocyanin and betacyanin pigments. To obtain the phytochemical content of a plant, an extraction process is carried out. The extraction method and solvent are factors that influence the amount of phytochemical content in the extract. There has been no research analyzing effective methods and solvents for extracting insulin leaves to obtain the highest antioxidant effect. This research was conducted to determine the effect of extraction methods and solvents on the antioxidant activity of insulin leaf extract. Maceration and digestion methods with distilled water, 50% ethanol and 96% ethanol were used in the extraction of insulin leaf simplicia in this study. Samples obtained were Aquadest Macerated Extract (EMA), 50% Ethanol Macerated Extract (EME50), 96% Ethanol Macerated Extract (EME96), Aquadest Digested Extract (EDA), 50% Ethanol Digested Extract (EDE50), and 96% Ethanol Digested Extract (EDE96). Testing the antioxidant activity of each sample used the DPPH method by calculating the IC50 value and using Quercetin as a positive control. Data analysis was carried out using one way anova analysis. The results show that the choice of solvent and extraction method influences the antioxidant activity of the extract. The IC50 values ​​for each extract from low to high are: EDA, EDE50, EMA, EDE96, EME50, and EME96, with values: 20.06ppm; 22.44ppm; 23.77ppm; 23.84ppm; 24.55ppm; and 27.71ppm. It can be concluded that the method and solvent to obtain the best antioxidant activity from insulin leaves (Smallanthus sonchifolius) is extraction using the digestion method with distilled water as a solvent (p<0,05). Keywords: antioxidant, digestion, insulin leaf, maceration, solvent